UKRAINIAN-MOLDOVAN RELATIONS DURING THE TIME OF BOHDAN KHMELNYTSKY IN THE CONTEXT OF THE SEARCH FOR INTERNATIONAL GUARANTEES OF UKRAINIAN INDEPENDENCE (Південний архів (історичні науки), 2025)
The purpose of the article is to conduct a scientific study of the Moldovan direction of Bohdan Khmelnytsky's foreign policy in the context of the formation of Ukrainian Cossack statehood in the mid-17th century. The author analyses the hetman's plans to legitimise his own power, attempts to establish dynastic ties and military-political alliances with the Principality of Moldova as one of the key factors in the implementation of his state-building strategy. The methodological basis of the article is the principles of objectivity, historicism, comprehensiveness, continuity, as well as a comparative analysis of diplomatic documents; a historiographical approach, which together allowed for a comprehensive study of the problem. The work uses an interdisciplinary approach, drawing on data from political history, the history of international relations, and social history. Results and conclusions. It has been established that Khmelnytsky's Moldavian project was an attempt to integrate the Hetmanate into the system of international relations in Eastern Europe through the dynastic marriage of his son Tymofiy to Rozanda Lupu. The aim was to raise the status of the Hetman dynasty to that of European monarchical houses and to ensure a stable rear in the struggle against the Polish-Lithuanian Commonwealth. Despite short- term successes, in particular the victory at Batog and the conclusion of the Ukrainian-Moldovan alliance, internal opposition in Moldova and external pressure from the Ottoman Empire, Transylvania and Poland led to the collapse of the plans. The defeat at Suceava in 1653 and the death of Tymofiy Khmelnytsky were key moments that forced the hetman to abandon the Moldavian vector and reorient his foreign policy towards an alliance with Muscovy and the Porte. The Moldavian project was an important component of Khmelnytsky's political strategy aimed at creating an independent Ukrainian state. Its failure demonstrated the dependence of hetman diplomacy on international circumstances and internal contradictions in neighbouring countries. The experience of these relations allows us to understand the complexity of the processes of Ukrainian statehood formation in the 17th century and to outline prospects for further research, particularly in the context of Ukrainian-Ottoman and Ukrainian-Transylvanian relations.
Keywords: Bohdan Khmelnytsky, Moldavian Principality, international relations, dynastic marriage, Battle of Batoh, Ukrainian statehood, 17th-century diplomacy